The finances of public enterprises - Ramanadham, V. V. (Bombay ; New York : Asia Pub. House, 1963)
This book discusses issues relating to finances of public enterprises with specific reference to: the contemporary problems of the profits of public enterprises; the profit criteria; the pricing policy of public enterprises; and financial organisations within public enterprise.
Includes bibliographical footnotes and index.
lje 28/09/2018
Loans
Keywords: Government corporations; India